The influence of drying on the physiological quality of crambe fruits - doi: 10.4025/actasciagron.v34i2.12482 - Lílian Moreira Costa; Osvaldo Resende; Douglas Nascimento Gonçalves; Kelly Aparecida Souza; Juliana de Fátima Sales; Juliana Rodrigues Donadon (Acta Scientiarum. Agronomy, 2011)
This study was performed to evaluate the physiological quality of Crambe abyssinica Hochst fruits subjected to drying under different treatments with air. The crambe fruits, with moisture content of 21.0 ± 1.3 (% w.b.), were manually collected and dried until their moisture content reached 7.0 ± 1.4 (% w.b.). The crambe fruits were dried with natural air (23°C mean temperature and 60.6% average relative humidity) and seven days after harvest in an experimental dryer with forced ventilation at temperatures of 30, 40, 50, 60 and 70°C and relative humidities of 37.4, 22.3, 14.0, 8.3 and 5.1%, respectively. The evaluation was the percent germination, the germination speed index (GSI), the amount of water absorption and the electrical conductivity. The results of the study showed that increases in the drying temperature decreased the drying time and negatively affected the quality of the fruits. The study’s findings for the GSI and for the percent germination showed that the drying temperature of 30°C yielded superior results. The moisture content of the crambe fruits after absorption was higher at the drying temperatures of 23, 40 and 70ºC. In contrast, the electrical conductivity measurement was unaffected by drying at high temperatures.